Produktutveckling av en storformatskamera - Toryd,Joel Niklas (2025)
This thesis has the goal of developing a modern interpretation of the old concept of large format cameras, through modern design and manufacturing processes. The overarching design framework for this thesis has been the Double Diamond method, a diverging and converging design process. A customer survey through interviews of users has led to a list of requirements, from which concepts were generated. During the design and prototyping process, several mechanical partial solutions were considered. Primarily with a focus on linear and rotational bearings fabricated with 3D-printing. After several iterations, a final prototype was produced. This prototype fulfilled the requirements of a proof of concept, and had all the basic features required to take test photographs. However, this prototype was not a complete minimum viable product, due to lacking resourses. For example, the different movements of the camera were not all lockable, which is a basic premise for cameras on the market. The final prototype is presented in the latter parts of the report, along with the test-pictures taken with it. It is also discussed which parts of the prototype that needs to be developed further to arrive at a prototype that is ready for the market. The result of the project is a physical proof of concept that fills a gap in the market for a lightweight, technologically sophisticated camera with several independent movements.
Keywords: Linear bearings; rotational bearings; 3D-printing; large format camera; product development methodology